Beutin (Pas-de-Calais) : une installation thermale domestique en pays morin - David Labarre (Gallia)
The site of the Camp Saint-Pierre in Beutin (Pas-de-Calais) is located on the north bank of the Canche Valley. The features observed during the excavation are related to a domestic thermal bath adjacent to a probable villa that appears to extend onto the adjacent plots. The observed remains follow on from a previous, poorly-defined occupation, marked by several pits and fragmentary elements. The objects retrieved from the infill of these vestiges date this occupation to the first half of the 1st c. AD. The excavation of the building brought to light two distinct occupation periods, divided into several construction phases. The first building lies on an artificial terrace and several indirect markers tend to demonstrate his bathing vocation: it is mainly about architectural elements observed in reuse in the thermal baths of the following period. We also note the presence of a semi-sunken area in the south-western half of the building, which probably corresponds to the imprint of a totally dismantled hypocaust. The dating elements associated with this first building are extremely tenuous. They allow, at best, to date the occupation between the 2nd c. and the beginning of the 3rd c. AD.After a period of non-formally identified use, the complex was totally destroyed. The materials derived from its demolition seem to correspond to a complete overhaul of the bath area associated with the villa, from now on divided into two distinct parts. The study concludes that a first circuit was designed around hypocaust 2183 (room 2) and a second associated with hypocausts 2131 and 2049 (rooms 7 and 9). The first seems to correspond to a classic bathing circuit with frigidarium, tepidarium and caldarium, whereas the second, organized around hypocausts 2049 and 2131 (rooms 9 and 7), seems to be reserved for physical activities. The ceramics found in the infills of the hypocausts show that this second building was abandoned between the end of the 3rd c. AD and the beginning of the 4th c. At the end of the study, several questions are still pending, and it is not possible to determine the type of establishment in which the thermal baths were found, or the exact role of the building before it was abandoned. However, the quality of the installation implies that the villa associated with the thermal baths must have been of a fairly high status and that it was located in a heavily settled strategic sector.